Life cycle assessment of direct recycling hot press forging of aluminium AA7075 metal matrix composite - Mohd Khaireez, Muhamad Haikal; Yusuf, Nur Kamilah; Atef M Ghaleb, Atef M Ghaleb; Sami Al-Alimi, Sami Al-Alimi; Aiman Rahmat, Aiman Rahmat; Ikhwan Shah Tisadi Tukiat, Ikhwan Shah Tisadi Tukiat; Saif, Yazid; Adham E Ragab, Adham E Ragab; Wenbin Zhou, Wenbin Zhou; Wadea Ameen, Wadea Ameen (2024)
The primary objective of this research is to investigate the process of direct recycling of AA7075 aluminium alloy, which is extensively utilised in the aerospace and flight sectors due to its exceptional strength and lightweight characteristics. Alumina (Al2O3)is used as a reinforcing agent and the effect of hot press forging (HPF) parameters on the mechanical characteristics and surface integrity of the metal matrix composite (MMC) constructed of AA7075 alloy with 1% Al2O3 has been studied. Furthermore, the utilisation of an integrated life cycle assessment(LCA) approach is implemented to assess the environmental impacts and economic expenses associated with the recycling of aluminium via high-pressure forming for both the metal matrix composite and AA7075 alloy. Response surface methodology (RSM)is applied to ascertain the optimal parameters for high-performance filtration. The findings suggest that employing a forging temperature of 532.34 °C and a holding time of 60 min produces favourable results. When comparing the characteristics of the MMC and recycled aluminium, it can be observed that they both demonstrate similar essential process attributes. The utilisation of HPF in conjunction with the Multi-Material Composite has the potential to yield a reduction of up to 24.97% in Global Warming Potential (GWP). This research demonstrates the efficacy of HPF as a viable approach for environmentally conscious and economically efficient recycling of AA7075 aluminium scrap, thereby improving product performance and promoting sustainability.